John Higgins on Academic Freedom. (April 2016) - Docherty, Thomas
This review article considers the work of John Higgins on academic freedom. It reveals that Higgins offers an account that eschews any fundamental relation between academic freedom and the market. Rather, he offers a more nuanced view that takes academic freedom out of the academy and into a wider political and social domain, while simultaneously avoiding the trap of offering a transcendent or metaphysical 'idea' of academic freedom. This depends upon what Higgins calls 'critical literacy', which requires that we develop an understanding of specific issues textually, theoretically, and historically. In this way, Higgins attends to historically specific occasions when social freedom is under threat, and demonstrates how our freedoms within the academy can intervene to redeem that social freedom and extend it. The piece argues that academic freedom is more than merely academic, but social and political.